PENGARUH PENGGUNAAN HEADSET TERHADAP GANGGUAN PENDENGARAN: TINJAUAN TERKINI DARI SATU DEKADE TERAKHIR - Triansyah, Irwan; Ade Teti Vani; Nadia Purnama Dewi; Aryaldy Zulkarnaini; Dessy Abdullah; Yanti Fitri Yasa; Muhammad Ivan (Nusantara Hasana Journal, 2025)
Headset usage has become increasingly common today, facilitating work and communication. However, prolonged use of headsets, especially at high sound frequencies, can damage the hair cells in the cochlea, leading to permanent hearing loss. This condition is known as Noise-Induced Hearing Loss (NIHL). This research employed a literature review of journals published between 2013 and 2025. The journals were searched using keywords such as "headphone hearing loss," "noise-induced hearing loss personal listening devices," "safe listening guidelines," and "hearing impairment headset." The search results were presented narratively. The study found that NIHL is prevalent across all continents and is closely associated with headset usage. Specifically, using headsets at high volumes and for extended periods can lead to NIHL. This issue is particularly significant among Generation Z, with various studies indicating instances of hearing loss. The study concluded that there is a direct relationship between hearing loss and headset use at sound levels exceeding 85 dB for more than 8 hours a day.